Tax Compliance in Bangladesh – A Structural Equation Modelling Approach - Hasan, Rashedul; Mohammad, Niaz; Alam, Mohammad Faridul (American Journal of Trade and Policy, 2017)
Tax compliance behavior has been researched at different times in various parts of the world using various theories. This research has focused on the psychological aspects of tax compliance behavior by applying the theory of planned behavior (TPB) proposed by Ajzen. 300 taxpayers were studied using a questionnaire based on Likert scale, and the results were analyzed using structural equation modelling. Results found from SEM approach indicate that subjective norm has a significant influence on tax compliance behavior while intention mediates it and moderated by religion. Attitude and perceived behavioral control were found to have a significant influence on intention. Individual taxpayers are selected from the capital, and thus findings derived from the sample might not be generalizable for all individual taxpayers in Bangladesh. The results of this study might provide some insight to the tax non-compliance problem in Bangladesh and help authorities to design strategies to motivate taxpayers to comply with existing fiscal policies. Tax compliance issues have been explored from various perspectives in Bangladesh. Lack of significant influence on subjective norm toward taxpayer intention indicates that social and peer is yet to make a substantial contribution to improving tax compliance. This study has introduced structural equation modelling technique to explore the moderating influence of religion on individual taxpayers in the context of Bangladesh.
Keywords: Theory of planned behaviour; Tax compliance; Structural Equation Modeling